A Peer Counselling Model for Use in Secondary Schools - Mcintyre, Douglas R.; Thomas, Gordon H.; Borgen, William A. (Canadian Journal of Counselling and Psychotherapy, 2012)
In this paper a peer counselling program piloted in Windermere Secondary School in Vancouver is described. Peer counselling is defined as a process where students are trained in helping skills to offer, under supervision, listening, support, and alternatives to other students. The procedures followed in implementing the program are discussed; these were identifying the needs of the school, setting program goals, marketing the program to administration, staff, students and parents, training and supervision, establishing peer counselling services, and evaluating the program. The summary and conclusions draw together the strengths and benefits of the program, and make recommendations based on the experience gained during the year.